Pengembangan Knowledge Management System Berbasis Cloud Pada Kelas Karyawan Universitas Pramita Indonesia - Hadidtyo Wisnu Wardani; Arief Wibowo (Universitas Budi Luhur, 2022)
Knowledge Management System (KMS) is very important to manage knowledge and tacit to have added value for the organization, especially the Pramita Indonesia Employee Class, related to the routines of all employees in the work unit who are expected to provide solutions in solving problems that occur. With conditions that often occur at this time, knowledge and experience have not been documented, the socialization of standard operating procedures is not running properly and the tenure of employees is unknown so when there is a change of employees in the organizational structure, it will result in the loss of knowledge and experience possessed by an employee, confusion or incomplete information received to create misunderstandings between employees in communicating. Based on the results of research that are following the conditions that exist in the class work unit of Pramita Indonesia employees, the author tries to develop a KMS model. By using the Tiwana model framework, and the Becerra-Fernandez progress structure research methodology, as well as using the SECI Nonaka model development, to test the framework model using the Gathering Conversation (FGD) and Black Box Testing strategies, and using a Likert scale for scoring the system test results. , and the quality of the KMS software prototype is 72% with the Very Appropriate category, so the results show that the overall KMS prototype has been running well so that the proposed system can be used in managing knowledge to provide maximum service solutions efficiently and effectively